Synthesis and characterization of sol gel derived nontoxic CZTS thin films without sulfurization. Issue 3 (8th January 2020) - Amrit, Pratyay; Jain, Surbhi; Tomar, Monika; Gupta, Vinay; Joshi, Bhawana
Abstract: Recently, great attention has been paid to the development of earth rich and nonhazardous Copper Zinc Tin Sulfide (CZTS–Cu2 ZnSnS4 ) thin films for application in photovoltaic devices owing to its high absorption coefficient over the visible and infrared region. However, sulfurization process is an indispensable step in growing stoichiometric thin film using conventional physical vapor deposition. Hence, it is imperative to devise a liquid based technique without intentional sulfurization for the optimum quality growth of CZTS thin films. In the current work, layer‐by‐layer sol‐gel deposition technique was utilized to grow high quality CZTS thin films without sulfurization and their structural and optical characteristics were investigated using XRD studies and UV‐visible spectroscopy respectively. The morphology and chemical composition of the prepared CZTS films are estimated by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) analysis respectively. Highly absorbing and crystalline CZTS films have been successfully grown in the present work which could be further utilized as an absorber layer in photovoltaic applications.